The recommendations for design, construction and maintenance of animals passages - a document unifying problems - Wysokowski, Adam (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
With the sustainable development of transport infrastructure can not ignore the environmental problems. This applies both to build much-needed new roads and railways, as well, as their modernization. For this purpose, it becomes essential to build passages for animals and culverts of complex function. The author of the paper moves the need for a unified Recommendations of Design, Construction and Maintenance of Animal Passages, which clearly organize all the issues associated with these objects. Currently such recommendations are being developed under the leadership of the author.